Differential reporting of drug use among gay, bisexual and transgender stimulant-using homeless adults post intervention. (4th March 2017) - Nyamathi, Adeline M.; Salem, Benissa E.; Farabee, David; Zhang, Sheldon
Abstract: Homeless gay and bisexual (G/B) men, and transgender female stimulant users are at high risk for continued substance use and dependency; yet, there is a limited understanding of reasons for differential reporting of drug use (defined as different outcomes of drug use when assessed by self-report versus urinalysis) post intervention among this population. This study examined self-reported drug use versus urinalysis reporting at four-month follow-up evaluation of a longitudinal study conducted among 166 G/B and transgender stimulant-using homeless adults. Follow-up data were collected from a two-group intervention focused on reducing stimulants and other illicit drug use as well as promoting HBV, HCV and HIV disease prevention. Findings of logistic regression revealed that transgender women and those who reported fair-or-poor health were more likely to self-report drug use which differed from the urinalysis biomarker. Amphetamines were the drugs most often differentially reported, possibly due to the fact that methamphetamine was cut with amphetamine or that the majority of the sample used methamphetamine which was metabolized into amphetamine. While the numbers of other drugs differentially reported were small, one-third to one half of the sample who were positive on urine testing for cocaine and opiates, respectively, did not report the use of these drugs. Findings highlight the need for biomarker assessment of drug use, especially post intervention.